Trouver place humaine dans le cosmos - Augustin Berque (EchoGéo)
Modernity may be qualified as a decosmization (a loss of the unitary and axiological order which integrated the human and the universal), the effect of which deprives of authenticity our relation with places, which from then on are no more than a screen where human activity projects itself. The example of Joël Bonnemaison, who at his death was dubbed a man-place by his friends in Tanna, may help us in conceiving the possibility of recomizing human existence.